Evaluation of Wind Energy Potential for Electricity Generation in Three Locations of Zanzibar, Tanzania - Hamza Khamis Kombo; Ridho Irwansyah; Nasruddin Nasruddin (International Journal Labs, 2025)
This study evaluates the wind energy potential for electricity generation in the North, South, and West regions of Zanzibar using wind speed data from NASA POWER (2014–2023). The Weibull statistical distribution indicated annual average wind speeds of 5.43 to 5.81 m/s. The South Region experienced the highest wind stability (k=7.97 in 2015), while the North had the greatest energy-carrying wind speed (6.80 m/s in 2020). Wind power density ranged from 107.87 to 132.98 W/m², and energy density varied from 944.91 to 1164.94 kWh/m²/year, confirming that all sites fall into Class 2 (Marginal) of the Pacific Northwest Laboratory standard—implying weak feasibility for large wind farms but suitability for small- to medium-scale or hybrid schemes. A technical-economic analysis of four turbines identified the De Wind D7 (1500 kW, 70 m hub height) as the most suitable, with the highest annual energy production (>1300 MWh/year) and capacity factor (>10%). The study provides crucial data to inform investments and policies for diversifying Zanzibar's energy mix and fostering sustainable development.